Hypertension and arterial stiffness in heart transplantation patients (Clinics, 2016)
OBJECTIVES: Post-transplantation hypertension is prevalent and is associated with increased cardiovascular morbidity and subsequent graft dysfunction. The present study aimed to identify the factors associated with arterial stiffness as measured by the ambulatory arterial stiffness index. METHODS: The current study used a prospective, observational, analytical design to evaluate a group of adult heart transplantation patients. Arterial stiffness was obtained by monitoring ambulatory blood pressure and using the ambulatory arterial stiffness index as the surrogate outcome. Multivariate logistic regression analyses were performed to control confounding. RESULTS: In a group of 85 adult heart transplantation patients, hypertension was independently associated with arterial stiffness (OR 4.98, CI 95% 1.06-23.4) as well as systolic and diastolic blood pressure averages and nighttime descent. CONCLUSIONS: Measurement of ambulatory arterial stiffness index is a new, non-invasive method that is easy to perform, may contribute to better defining arterial stiffness prognosis and is associated with hypertension.